CALCULATION AND MEASUREMENT OF THE EMITTING LIGHT FROM EXCITING ARGON ATOMS BY BETA PARTICLES OF TRITIUM - Said Selman Kamoon (Journal of Madenat Alelem University College, 2015)
The range of β-particles in a mixture of gases can be fitted to be less than a certain value if the weight percent of the mixture is chosen with suitable values. The present work shows that when the emitted beta-particles from Tritium (T) gas pass through a mixture of Argon (Ar),Tritium (T) ,deuterium (D) and nitrogen (N) gases, such that, the weight percent of the mixture (MAr/MT) is chosen to be about 10 (the weight percent of the Argon is about 82% of the mixture),the mass of the Deuterium is equal to the mass of Tritium and the mass of Nitrogen is 0.01 of the mass of Argon, then the range of β-particles is less than (1 cm) ,and the emitting light from exciting Argon atoms is so enough to detect by EM9530B photomultiplier tube.